2008
DOI: 10.1113/jphysiol.2007.141580
|View full text |Cite
|
Sign up to set email alerts
|

Genetic predisposition to hypertension sensitizes borderline hypertensive rats to the hypertensive effects of prenatal glucocorticoid exposure

Abstract: An adverse intrauterine environment can increase the incidence of hypertension and other cardiovascular disease risk factors. However, in clinical and experimental studies the magnitude of the effect is variable. Possibly, the relative influence of the prenatal environment on cardiovascular disease is determined in part by genetic factors that predispose individuals to the development of environmentally induced hypertension. We tested this hypothesis by comparing the effects of prenatal dexamethasone treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 58 publications
(184 reference statements)
1
4
0
Order By: Relevance
“…However, in this study we observed significant genotype-related differences in the activation of the HPA axis as determined by pCort concentration. In agreement with previously published studies, we observed a higher basal corticosterone concentration in young SHR animals compared to the WKY strain [ 36 ] but not in BHR [ 37 ]. Regarding the effect of stress, the main effect of crowding on pCort concentration was significant, but the most pronounced increase was observed in BHR, suggesting that young females of this genotype are particularly sensitive to this stressor.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, in this study we observed significant genotype-related differences in the activation of the HPA axis as determined by pCort concentration. In agreement with previously published studies, we observed a higher basal corticosterone concentration in young SHR animals compared to the WKY strain [ 36 ] but not in BHR [ 37 ]. Regarding the effect of stress, the main effect of crowding on pCort concentration was significant, but the most pronounced increase was observed in BHR, suggesting that young females of this genotype are particularly sensitive to this stressor.…”
Section: Discussionsupporting
confidence: 93%
“…Bechtold et al [ 41 ] found that endogenous corticosterone acts via hindbrain glucocorticoid receptors (GR) to enhance the pressor response to stress in adult BHR males but promotes adaptation in WKY. Moreover, prenatal dexamethasone treatment (a synthetic glucocorticoid analogue) increased baseline arterial pressure selectively in BHR in both sexes, but pCort increased only in female BHR [ 37 ]. With respect to our results, we assume that a similar corticosterone-mediated mechanism could be responsible for the differential effects of crowding on BP development in young WKY and BHR females.…”
Section: Discussionmentioning
confidence: 99%
“…However, the magnitude of the HR, MAP and DBP increases in the DEX exposed group are smaller, and in most instances not larger than the stated accuracy of the telemetry transmitter (±3 mmHg) suggesting that DEX has not programmed overt hypertension. The development of hypertension in adult life after prenatal exposure to glucocorticoids is a common finding [18], [26], [36], [43], [51], although this is not always the case [27], [52], [53]. In this regard, it is important to note that the use of methods such as tail-cuff plethysmography or carotid cannulation to measure blood pressure, may elicit a stress response and thus not truly reflect elevations in basal blood pressure [28], though repeated handling and conditioning of the animal through multiple, repeated measurements made by experienced experimenters may minimize the effects of these stresses and still yield valuable data.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors such as recovery from anesthesia, or preheating of the tail have the potential to lead to physiological alterations in the animal's cardiovascular system and a subsequent a rise in blood pressure. Indeed, in a number of studies (in sheep, monkeys and rats) where blood pressure was measured using non-invasive radiotelemetry there was no evidence of a hypertensive phenotype in the offspring that had been parentally exposed to DEX [27], [52], [53]. Alternatively, O'Regan et al reported that their DEX exposed rat offspring were hypotensive relative to the control group, that the male offspring also had an exaggerated blood pressure response to a restraint stress, and were less active [27].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the use of an invasive catheter could be a limitation of coronary artery DSA, but we note that indwelling catheters are possible(Bechtold, Vernon et al 2008) that will allow such studies to become longitudinal.…”
Section: Discussionmentioning
confidence: 99%